Predicted molecules and signaling pathways for regulating seizures in the hippocampus in lithium-pilocarpine induced acute epileptic rats: A proteomics study - Wang, Peng; Yang, Lu; Yang, Rang; Chen, Zhangping; Ren, Xiaofan; Wang, Fangjiao; Jiao, Yan; Ding, Yuxin; Yang, Fengyuan; Sun, Tao; Ma, Huisheng (Frontiers in Cellular Neuroscience, 2022)
Seizures in rodent models that are induced by lithium-pilocarpine mimic human seizures in a highly isomorphic manner. The hippocampus is a brain region that generates and spreads seizures. In order to understand the early phases of seizure events occurring in the hippocampus, global protein expression levels in the hippocampus on day 1 and day 3 were analyzed in lithium-pilocarpine induced acute epileptic rat models using a tandem mass tag-based proteomic approach. Our results showed that differentially expressed proteins were likely to be enhanced rather than prohibited in modulating seizure activity on days 1 and 3 in lithium-pilocarpine induced seizure rats. The differentially regulated proteins differed on days 1 and 3 in the seizure rats, indicating that different molecules and pathways are involved in seizure events occurring from day 1 to day 3 following lithium-pilocarpine administration. In regard to subcellular distribution, the results suggest that post-seizure cellular function in the hippocampus is possibly regulated in a differential manner on seizure progression. GO annotation results showed that, on day 1 following lithium-pilocarpine administration, it is likely necessary to regulate macromolecular complex assembly, and cell death, while on day 3, it may be necessary to modulate protein metabolic process, cytoplasm, and protein binding. Protein metabolic process rather than macromolecular complex assembly and cell death were affected on day 3 following lithium-pilocarpine administration. The extracellular matrix, receptors, and the constitution of plasma membranes were altered most strongly in the development of seizure events. In a KEGG pathway enrichment cluster analysis, the signaling pathways identified were relevant to sustained angiogenesis and evading apoptosis, and complement and coagulation cascades. On day 3, pathways relevant to Huntington’s disease, and tumor necrosis factor signaling were most prevalent. These results suggest that seizure events occurring in day 1 modulate macromolecular complex assembly and cell death, and in day 3 modulate biological protein metabolic process. In summary, our study found limited evidence for ongoing seizure events in the hippocampus of lithium-pilocarpine induced animal models; nevertheless, evaluating the global differential expression of proteins and their impacts on bio-function may offer new perspectives for studying epileptogenesis in the future.